Understanding The Ruling Of The Constitutional Court No: 90/PUU-XXI/2023 From A Civil Law And Common Law Perspective - Endro Satoto; Zainal Arifin Hoesein (International Forum of Researchers and Lecturers, 2024)
To ensure legal certainty in a country, various countries in the world have different legal systems which are acclimated to the needs and characteristics of each country. In general, two legal systems are commonly applied, namely the civil law legal system and the common law legal system. The civil law system is a legal system that originates from mainland Europe and is based on Roman law with the main characteristic being the existence of a codification system of the main legal principles. The three primary features of civil law legal systems are codification, non-precedential judges, and an inquisitorial judiciary. Meanwhile, the common law system is a system that refers to customs in England that are not written down and which through judge decisions are then made legally binding. The choice of the legal system will affect the preparation of legal products and the results decided. The choice of legal system significantly impacts legal products produced, whether regulations or jurisprudence. Indonesia's recent Constitutional Court verdict (90/PUU-XXI/2023) is raising concerns over its legitimacy and potential impact on the country's legal framework. Further analysis and scrutiny are necessary.